Dispute Resolution in Unwritten Agreements in Connection of Cooperation Reviewed from a Civil Law Perspective - Ria Juliana Siregar; Martono Anggusti; Rio Saputra Manullang (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2026)
This study aims to describe the regulation of agreements according to Indonesian contract law (KUHPerdata), which then analyzes the legal force of agreements made orally and their proof in court. This research is a normative juridical research conducted with a statutory and conceptual approach. The results of the study indicate that agreements are specifically regulated in the Civil Code, Book III, Chapter II concerning